2004
DOI: 10.12968/ijtr.2004.11.7.13359
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the role of the rehabilitation assistant

Abstract: The aim of this study was to evaluate the role of the rehabilitation assistant: a junior multidisciplinary grade combining key elements from nursing, occupational therapy, physiotherapy and speech and language therapy. The authors analysed daily activities, sophistication of clinical thinking and functioning of the role using timesheets, the think-aloud technique and semi-structured interviews. Rehabilitation assistants were found to facilitate rehabilitation and extend therapists' roles. Mobility, washing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 11 publications
0
28
0
Order By: Relevance
“…To address this, strategies, such as collaborative learning, have been employed to include the health assistant into models of care. Education has been highlighted as essential for the successful implementation of new models of care, and clear role delineation appears to be an aspect of delivering successful programmes . These strategies have been found to be effective; however, there is little information currently regarding the appropriateness of these strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this, strategies, such as collaborative learning, have been employed to include the health assistant into models of care. Education has been highlighted as essential for the successful implementation of new models of care, and clear role delineation appears to be an aspect of delivering successful programmes . These strategies have been found to be effective; however, there is little information currently regarding the appropriateness of these strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Education has been highlighted as essential for the successful implementation of new models of care, 21,22 and clear role delineation appears to be an aspect of delivering successful programmes. 23,24 These strategies have been found to be effective; however, there is little information currently regarding the appropriateness of these strategies. Appropriateness can be defined as 'the extent to which an intervention or activity fits with or is apt in a situation' (p. 210).…”
Section: Introductionmentioning
confidence: 99%
“…Knight et al evaluated the role of rehabilitation assistants and found that the assistant’s role served to link all the disciplines within the multidisciplinary team and integrate community rehabilitation 20. The team leaders felt that inclusion of assistants in the team would improve the quality of service by being more patient-focused.…”
Section: Benefits Of Introducing Ahas Within the Allied Health Workforcementioning
confidence: 99%
“…12,13 The vocational qualifications of the AHA, which combines generic academic core modules and work-based learning, allows the AHA to have a broad spectrum of knowledge and skills necessary to prepare them for work with patients, carers and the relevant professionals or specialists. 14 Published research has highlighted numerous benefits of AHAs that include serving as a link across disciplines within a multi-disciplinary team, 15 the ability to work with patients to provide support, supervision and monitoring of their progress, 16 the ability to provide consistent and goal directed rehabilitation 17 and improvements in patient compliance and patient clinical outcomes. 18 The rapidly expanding area of telerehabilitation, i.e.…”
Section: Introductionmentioning
confidence: 99%